PENGETAHUAN PAJAK DAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI: TINJAUAN LITERATUR INTEGRATIF - Intan Irmadela; Fanji Farman (PT. Berkah Digital Teknologi, 2026)
Purpose: This study integrates evidence on how tax knowledge contributes to individual taxpayer compliance and identifies the mechanisms and boundary conditions underlying this relationship. Research methodology: An integrative literature review was conducted using peer-reviewed studies, conceptual articles, and authoritative institutional documents published primarily during 2016-2026. The synthesis combined tax behavior, administration, and digital-system perspectives. Results: Tax knowledge is a multidimensional capability comprising declarative, legal, procedural, and digital knowledge. It supports compliance through cognitive clarity, compliance self-efficacy, awareness, fairness appraisal, and trust. Its effect depends on regulatory complexity, service and system quality, economic capacity, policy stability, and institutional legitimacy. Limitations: The review is integrative rather than exhaustive, and heterogeneity in constructs, samples, and outcomes prevents effect-size aggregation. Contribution: The study replaces a simple direct-effect view with a mechanism- and context-based framework that guides segmented taxpayer education, service design, and future empirical testing. Keywords: tax knowledge; individual taxpayer; tax compliance; tax education; digital taxation; voluntary